2022
DOI: 10.1155/2022/3243647
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Promotes Pancreatic Ductal Adenocarcinoma Gemcitabine Resistance and Invasion through Modulating ROS/MMP-3 Signaling Pathway

Abstract: Pancreatic ductal adenocarcinoma (PDA) is often concomitant with diabetes mellitus, which mainly manifests as an increased blood glucose level. Previous studies revealed that diabetic status reduced the survival and blunted gemcitabine sensitivity in PDA patients. This study is aimed at analyzing the mechanism of elevated gemcitabine resistance and cancer invasion ability under high glucose environment. We selected 129 patients with 22 surgical resected samples from 2015 to 2021, who underwent pancreatic surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…For example, hyperglycemia fosters tumor cell growth by creating a nutrient‐rich environment and by promoting the resistance of PC cells to gemcitabine through the regulation of the ROS/MMP‐3 signaling pathway. 36 Moreover, hyperglycemia fuels the proliferation of PC cells through the induction of EGF expression and EGFR activation. 37 In contrast, a few studies found comparable prognosis between PC patients with or without diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hyperglycemia fosters tumor cell growth by creating a nutrient‐rich environment and by promoting the resistance of PC cells to gemcitabine through the regulation of the ROS/MMP‐3 signaling pathway. 36 Moreover, hyperglycemia fuels the proliferation of PC cells through the induction of EGF expression and EGFR activation. 37 In contrast, a few studies found comparable prognosis between PC patients with or without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, hyperglycemia may promote malignant phenotype of cancer cells. For example, hyperglycemia fosters tumor cell growth by creating a nutrient‐rich environment and by promoting the resistance of PC cells to gemcitabine through the regulation of the ROS/MMP‐3 signaling pathway 36 . Moreover, hyperglycemia fuels the proliferation of PC cells through the induction of EGF expression and EGFR activation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HIF-1α binds to the HRE on the fascin promoter and activates its mRNA transcription, and overexpression of fascin can increase MMP-2 expression and promote PC cell migration and invasion 357 . Moreover, ROS/MMP-3 signaling pathway is activated by high glucose and up-regulates ribonucleotide reductase catalytic subunit M1 (RRM1) expression, a member of ribonucleoside reductase, inducing gemcitabine resistance in PC 358 . MT1-MMP up-regulates the expression of high mobility group A2 (HMGA2), a non-histone DNA-binding nuclear protein involved in chromatin remodeling and gene transcription, to attenuate the therapeutic effect of gemcitabine in PC 359 .…”
Section: Introductionmentioning
confidence: 99%